Relationship between tree species richness and climate change in southeastern Mexico - Santillán-Fernández, Alberto; Escobar-Castillo, Judith; Ireta-Paredes, Arely del Rocío; Espinosa-Grande, Ezequiel; Bautista-Ortega, Jaime; Chávez-Vergara, Bruno Manuel (Instituto de Ecología, A.C., 2021)
The southeast of Mexico is the region with the greatest wealth of tree species in the country and potentially vulnerable to the effects of the future climate, therefore, the objective of this work was to relate the species richness and its modification to a climate change scenario in the southeast of Mexico. To this end, the current potential distribution and climate change of 760 tree species were modeled using MaxEnt. Currently, the temperature negatively increases the potential distribution of the species. Climate change models by 2050 suggest an increase in temperature, whereby tree cover will be reduced; in the case of species that coexist in the rainforest, they would be concentrated in the center of the region, while for temperate forest species, a reduction > 95% of the current area is forecast. However, it was observed that the areas where a greater number of species coexist tend to develop a smaller contraction of their range in the face of future climatic variations.